2022
DOI: 10.1097/mph.0000000000002447
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Endocrine Disorders in Childhood Brain Tumors From a Single Tertiary Center in Malaysia

Abstract: Patients with childhood brain tumors are at risk of endocrine disorders. The prevalence of endocrine disorders varies across the world but is unknown in Malaysia. This study’s objectives were to determine the prevalence of endocrine disorders among children with brain tumors in Malaysia and to identify endocrinopathy-associated risk factors. We retrospectively reviewed the clinical data of pediatric patients with brain tumors diagnosed and treated at the University Malaya Medical Center from 1 January 2001 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…The prevalence of endocrine disorders among childhood brain tumour survivors (CBTS) in our centre was 62% which was almost similar to a local study conducted in Klang valley by Ng et al, 61%. 8 Our prevalence was higher compared to other studies done in South Korea (37.1%), Netherlands (22.1%) and United States (49%). 2 , 9 , 10 Studies by Clement et al, in the Netherlands excluded patients with craniopharyngioma or a pituitary gland tumour while our study not only included all childhood brain tumour survivors, but also all types of endocrine complications such as obesity, growth, pubertal disorders and water/salt disturbances.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…The prevalence of endocrine disorders among childhood brain tumour survivors (CBTS) in our centre was 62% which was almost similar to a local study conducted in Klang valley by Ng et al, 61%. 8 Our prevalence was higher compared to other studies done in South Korea (37.1%), Netherlands (22.1%) and United States (49%). 2 , 9 , 10 Studies by Clement et al, in the Netherlands excluded patients with craniopharyngioma or a pituitary gland tumour while our study not only included all childhood brain tumour survivors, but also all types of endocrine complications such as obesity, growth, pubertal disorders and water/salt disturbances.…”
Section: Discussioncontrasting
confidence: 70%
“…Ng et al, reported ACTH deficiency was the most prevalent (37%) followed by hypothyroidism (35%) and CDI (21%). 8 In other parts of the world, the commonest hormonal deficiency was GHD that ranged from 12 to 58% and this pattern was seen more consistently compared to other hormonal deficiencies, [17][18][19] Short stature (46%) was the most common clinical presentation seen in our centre and the causes could be multifactorial, such as specific hormonal deficiency secondary to GHD, hypothyroidism, ACTH deficiency, poor nutrition, familial short stature or constitutional delay in growth and puberty (CDGP). 19 This finding was also reported by Gurney et al, and Pasqualini et al 20,21 Despite it being the most common manifestation, not all the CBTS were referred to endocrine unit for screening of the specific hormonal deficiency which might be due to poor awareness among the primary doctors.…”
Section: Subjects and Proceduresmentioning
confidence: 78%
See 2 more Smart Citations